Use of healthcare before and after sepsis in Sweden: a case–control study - Jacob Dahlberg; Adam Linder; Lisa Mellhammar (BMJ Open)
Objectives The aim of this study was to compare readmissions and death between sepsis and non-sepsis hospitalisations the first year after discharge, and to investigate what diagnoses patients with sepsis present with at readmission. The aim was also to evaluate to what degree patients hospitalised for sepsis seek medical attention prior to hospitalisation.Design Retrospective case–control study with data validated through clinical chart review. A disproportionate stratified sampling model was used to include a relatively larger number of sepsis hospitalisations.Setting All eight public hospitals in region Scania, Sweden (1 January to 3 December 2019).Participants There were 447 patients hospitalised for sepsis (cases), and 541 hospitalised for other causes (control) identified through clinical chart review.Outcome measures Cox regression was used to analyse readmission and death the year after discharge, and logistic regression was used to analyse healthcare the week prior to hospitalisation. Both analyses were made unadjusted, and adjusted for age, sex and comorbidities.Results Out of patients who survived a sepsis hospitalisation, 48% were readmitted the year after discharge, compared with 39% for patients without sepsis (HR 1.50, 95% CI 1.03 to 2.19), p=0.04. The majority (52%) of readmissions occurred within 90 days and 75% within 180 days. The readmissions were most often caused by infection (32%), and 18% by cardiovascular disease. Finally, 34% of patients with sepsis had sought prehospital contact with a physician the week before hospitalisation, compared with 22% for patients without sepsis (OR 1.80, 95% CI 1.06 to 3.04), p=0.03.Conclusion Patients hospitalised for sepsis had a higher risk of readmission the year after discharge compared with patients without sepsis. The most common diagnoses at readmission were infection followed by cardiovascular disease. With better follow-up, some of these readmissions could potentially be prevented. Patients hospitalised for sepsis had sought prehospital contact the week prior to hospitalisation to a greater extent than patients without sepsis.